COMBINED FLOW OF AN EXOTHERMIC FLUID WITH ELECTROKINETIC EFFECT OVER A MICROCHANNEL - Hamza, Muhammed Murtala; Ojemeri, Godwin; Maigemu, Mohammed Dago; Shuaibu, Abdulsalam; Usman, Idris Omakwu; Germache, Haruna Ishaya; Dazi, Jeremiah Aaron (FUDMA JOURNAL OF SCIENCES, 2025)
The steady state analysis of chemically reacting heat transfer problem of mixed convection flow in a vertical microchannel that is fully developed and embedded with electro-kinetic effect is performed in this article. The energy, electric potential, and momentum equations are solved in non-dimensional form under unequal wall zeta potentials, employing the homotopy perturbation method (HPM). The basic flow behavior of electric potentials, temperature, and velocity is investigated as a function of regulating parameters such as the Debye-Huckel parameter, mixed convection parameter, chemical reaction parameter, and rarefaction parameter. The findings are carefully examined and graphically represented in a number of illustrative plots. It was found that raising the levels of mixed convection, chemical reaction, and rarefaction parameters causes the fluid flow to escalate while the function of viscous heating term is to speed up the fluid temperature. Additionally, mounting values of Debye–Hückel parameter retards the electric potential in the micro-channel. Also, when the mixed convection, chemical reaction, electric potential, and streaming potential factors are ignored, the numerical computations of this findings are consistent with the previously published results.